Transcatheter Aortic Valve Implantation for Severe Pure Aortic Regurgitation with Dedicated Devices - Pierluigi Costanzo; Paul Bamborough; Mark Peterson; Djeven J Deva; Geraldine Ong; Neil Fam (Interventional Cardiology: Reviews, Research, Resources)
Aortic regurgitation (AR) is not the most common valvular disease; however, its prevalence increases with age, with more than 2% of those aged >70 years having at least moderate AR. Once symptoms related to AR develop, the prognosis becomes poor. Transcatheter aortic valve implantation for patients with pure severe AR and at prohibitive surgical risk is occasionally performed, but remains a clinical challenge due to absence of valvular calcium, large aortic root and increased stroke volume. These issues make the positioning and deployment of transcatheter aortic valve implantation devices unpredictable, with a tendency to prosthesis embolisation or malposition. To date, the only two dedicated transcatheter valves for AR are the J-Valve (JC Medical) and the JenaValve (JenaValve Technology). Both devices have been used successfully via the transapical approach. The transfemoral experience is limited to first-in-human publications and to a clinical trial dedicated to AR, for which the completion date is still pending.